Object-oriented sequence-domain representation of transformers for network analysis. - Enns, M.K (IEEE Transactions on power systems)
An object-oriented admittance matrix representation of transformers with any number of circuits is developed for direct use in modern network analysis programs. An analysis of manually adjusted and load-tap-changing taps shows that the effective impedance can vary by 2:1 over the full range of taps and should therefore be considered-for accurate network studies. The principal innovation lies in the preservation of the neutral nodes of Y-connected circuits by including their axes in the admittance matrix. This makes it possible to attach neutral impedances and connections to the neutral points, retaining their identities also instead of modifying the transformer zero-sequence parameters to account for them. Conversion of the transformer admittance matrix to engineering units makes it possible to use neutral impedances in ohms without conversion to any per-unit base